Synthesis, Densification and Characterization of Boron Carbide - Sonber, J.; Murthy, T.; Subramanian, C.; Fotedar, Ravi; Hubli, R.; Suri, A. (2013)
This paper presents the experimental results on synthesis of boron carbide from its elements. Boron to carbon ratio of 4:1 and a synthesis temperature of 1850°C was found optimum to obtain stoichiometric B4C. Higher boron in charge resulted in the formation of boron rich phase B8C along with B4C but was not effective in eliminating free carbon in the product. Effect of hot pressing parameters on densification of boron carbide was investigated and the optimum operating parameters to obtain B4C pellets with a density of =95% TD were identified. Mechanical and thermal properties were characterized and compared with literature values.